A bi-level programming model for oilfield development and its solution algorithm based on interactive intuitionistic fuzzy method - Min, Chao; Hu, Yanjie; Hou, Chunhua; He, Jing; Liu, Zhibin (Procedia computer science, 2019)
A bi-level programming model is constructed for the oilfield development in this paper with the objective to maximize the total benefit. The management level of the oil company is regarded as the leader in this model, which makes the global programming and assigns the allocated investments to four oilfield development modes (the follower). The lower levels work out their own optimized plans according to the tasks and the investment constraints, and then feed back to the upper level. To solve this mixed integer nonlinear programming problem, the Interactive Intuitionistic Fuzzy methods are employed to obtain the solution by combining with the intuitionistic fuzzy sets and establishing a scoring function. A practical example from some Oilfield in China is used to illustrate the application of the method for the “14th Five-year Plan”.